Prospects and challenges of perovskite type transparent conductive oxides in photovoltaic applications. Part I – Material developments. (1st November 2016) - Riza, Muhammad Arif; Ibrahim, Mohd Adib; Ahamefula, Ubani Charles; Mat Teridi, Mohd Asri; Ahmad Ludin, Norasikin; Sepeai, Suhaila; Sopian, Kamaruzzaman
Abstract: Transparent conductive oxides (TCOs) have been used in a wide variety of applications as sensors and electronic displays and for solar harvesting for the past decades. TCOs are made of conductive materials such as metals. Many studies have been conducted to improve the properties of materials for TCOs. The properties that make a TCO effective are high transmittance and low resistivity. The current commercialized TCO is indium tin oxide (ITO), which has excellent transmittance and lower resistivity than other TCOs such as zinc oxide. Indium is expensive as its availability is becoming more limited over time. As such, studies to find an alternative material to ITO are continuing. Perovskite-structure materials are a candidate material with acceptable optoelectric properties. Perovskites have a wide band gap of ∼3.0 eV and high transmittance along with exceptionally low resistance. The first part of this paper mainly discusses the progress and development of perovskite-structured TCO as well as materials modification by doping.